Bright chemiluminescent dioxetane probes for the detection of gaseous transmitter H2S. (15th August 2021) - Zhang, Zheng; Lin, Yuxing; Li, Zhenzhen; Dong, Gaopan; Gao, Yuqi; Ma, Siyue; Li, Jie; Du, Lupei; Li, Minyong
Graphical abstract: Abstract: Hydrogen sulfide (H2 S), the third gaseous transmitter after CO and NO, is a double-edged sword in the human body. A specific concentration of H2 S can attenuate myocardial ischemia–reperfusion injury by preserving mitochondrial function, in contrast, cause illness, including inflammation and stroke. There are already some probes for the real-time monitoring of the level of H2 S in the biological environment. However, they have some disadvantages, such as phototoxicity, low sensitivity, and low quantum yield. In this research, by linking 4-dinitrophenyl-ether (DNP), a specific recognition group for H2 S, with a chemiluminophore 1, 2-dioxetane, we designed and synthesized the probe SCL-1. To tackle the barrier that the traditional chemiluminescent group has a short emission wavelength and is not easy to penetrate deep tissues, an acrylonitrile electron-withdrawing substituent was installed to the ortho -position of the 1, 2-dioxanol hydroxy group. According to the same design strategy as SCL-1, the probe SCL-2 was designed with the modified chemiluminescent group. Studies have shown that SCL-2 with electron-withdrawing acrylonitrile has higher luminescence quantum yield and high sensitivity than SCL-1, realizing real-time detection of H2 S in vitro and in vivo. The LOD of SCL-2 was 0.185 μM, which was the best among the currently available luminescent probes for detecting H2 S. We envisage that SCL-2 may be a practical toolbox for studying the biological functions of H2 S and H2 S-related diseases.